Forest diversity effects on insect herbivores: do leaf traits matter? - Muiruri Evalyne W.; Barantal Sandra; Iason Glenn R.; Salminen Juha-Pekka; Perez-Fernandez Estefania; Koricheva Julia (Blackwell, 2022)
Insect herbivore damage and abundance are often reduced in diverse plant stands. However, few studies have explored whether this phenomenon is a result of plant diversity effects on host plant traits. We explored indirect effects of tree species diversity on herbivory via changes in leaf traits in a long-term forest diversity experiment in Finland. We measured 16 leaf traits and leaf damage by four insect guilds (chewers, gall formers, leaf miners and rollers) on silver birch (Betula pendula) trees growing in one-, two-, three- and five-species mixtures. A decline in the frequency of birch in mixed stands resulted in reduced leaf area. This, in turn, mediated the reduction in chewing damage in mixed stands. In contrast, associational resistance of birch to leaf miners was not trait-mediated but driven directly by concurrent declines in birch frequency as tree species richness increased. Our results show that leaf trait variation across the diversity gradient might promote associational resistance, but these patterns are driven by an increase in the relative abundance of heterospecifics rather than by tree species richness per se. Therefore, accounting for concurrent changes in stand structure and key foliar traits is important for the interpretation of plant diversity effects and predictions of associational patterns.